PENGARUH AKUISISI TERHADAP PROFITABILITAS PERUSAHAAN PENGAKUISISI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Saputri, Devi Septian; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
In this research, the source of data has been done by using secondary data which has been obtained from Indonesia Stock Exchange. This research uses companies which have conducted acquisition in 2012. The sample collection method has been done by using purposive sampling and it should be in accordance with the determined criteria. The analysis which has been carried out to test the hypothesis in this research is quantitative analysis and different test of paired sample t test. The normality test and data homogeneity should be carried out before the different test. The result of the test which has been done by using paired sample t test shows that there is an insignificant increase on gross profit margin, there is a significant decrease on net profit margin, return on investment, return on equity and there is an insignificant decrease the rent-ability of economy on the non-financial companies which have conducted the acquisition in 2012.Keywords: Acquisition, Profitability Ratio, Non-Financial Company.